HUBUNGAN MANAJEMEN PERAN PERAWAT DENGAN PENANGGULANGAN PENYAKIT TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS LATERI KECAMATAN BAGUALA KOTA AMBON - Dewi Arwini Bugis; Bella Marchalina Nasarany (Pasapua Health Journal, 2022)
Introduction: Management is a dynamic proactive approach in carrying out an activity in an organization. This management includes planning, actualing, controlling (POAC) activities for staff, facilities and infrastructure in achieving organizational goals. Management in nursing is to support all aspects of nursing practice itself. Methods: This study uses a descriptive analytical method. The independent variable is management of the nurse’s role and the dependent variable is the prevention of pulmonary tuberculosis. This research was conducted in November 2021. The sample in this study was selected using a total sampling technique with a Cross Sectional Study approach and a total of 30 samples. The statistical test used is Chi-Square ɑ = 0.05. Results: Shows that there is a significant relationship between the management of the nurse’s role and the management of pulmonary TB in the working area of the Ambon Lateri Public Health Center, Baguala District ɑ = 0.002. Conclusion: There is a significant relationship between the management of the role of nurses and the management of pulmonary TB in the Work Area of the Lateri Community Health Center, Baguala District, Ambon City.